Professional Development of School Leaders In Supporting Effective Teaching And Learning In The Shiselweni Region, Eswatini (International Journal of Scientific Research and Management (IJSRM), 2022)
The study investigated how professional development of school leaders may support effective teaching and learning in the Shiselweni region of Eswatini. This was achieved through the following research objectives; to identify skills that school leaders have gained through professional development in their efforts to support teaching and learning activities; to determine how teachers perceived school leaders support as a result of their professional development for quality teaching and learning; to examine the challenges faced by school leaders as they transfer the skills gained through professional development and; to ascertain strategies for effective professional development which in turn supports teaching and learning. Using the mixed method approach, data was collected through interviews and questionnaires. Content analysis was used to analyse qualitative data and SPSS version 20 package was used to calculate frequencies and percentages which were used to analayse quantitative data. The findings of the study revealed the following; (1) School leaders acquire relevant managerial skills through professional development like instructional leadership, financial, personnel and organizational management. (2) There is a general agreement that school leaders empower teachers through in house and teacher training workshops. (3) School leaders are challenged in many ways such as financial constraints, limited resources and teachers’ resistance to change. (4) If properly trained and using a more structured approach, schools would benefit from instructional leadership, peer supervision of school leaders, performance appraisals and wellness programmes. The study recommended that (1) MoET should develop a policy on professional development of school leaders and teachers for more accountability on what has been gained. (2) There is need for a content-focused curriculum linked to effective teaching and learning. (3)Schools must develop their own capacity to learn through couching, mentoring, adopt to change and SLOs approach. (4) Shared leadership and collaboration at different levels of the school system should be encouraged as strategies for enhancing effective teaching and learning. Finally, it is recommended that INSET should conduct a needs assessment to ensure that the training is not ad-hoc and that the personnel should further their studies in institutions of higher learning.